Penggunaaan Metode Ancak Dalam Menganalisis Usaha Produksi Rumput Laut Di Desa Pekandangan Timur Kecamatan Bluto Kabupaten Sumenep - Mohammad Taufiq Hidayat (Universitas Islam Madura, 2022)
Optimizing efforts to increase food security requires innovation in increasing the effectiveness of commodity flows through better coordination. One of the Indonesian commodities that has great potential but has so far received little attention is Seaweed, which is one of the most widely produced and consumed plant commodities in Indonesia. This study aims to determine the efficiency of seaweed farming in Pekandangan East Village, Bluto District, Sumenep Regency. The analysis used in this study using Revenue Cost Ratio (R/C) is cost efficiency. The results of the research on the efficiency of seaweed cultivation in Pekandangan East Village, Bluto District, Sumenep Regency are: fixed costs in seaweed farming are Rp. 1575000 and variable costs are Rp. 316000 so the total cost of seaweed farming is Rp. 1891000, revenue is Rp. 540000 and profit is Rp. 1351000. The value of R/C Ratio > 1, which is 2.50, means that seaweed production farming in Pekandangan Timur Village, Bluto District, Sumenep Regency, efficient and profitable because with a capital of 2.00 you will get a profit of Rp. 2.50.